First and second person forms as resources for open reference and participation in Finnish everyday conversations - Helasvuo, Marja-Liisa; Suomalainen, Karita (John Benjamins Publishing Company, 2026)
Based on data from Finnish conversational interaction, this article explores the use of 1st and 2nd person forms in creating deictically nonspecific, open reference. We focus on the linguistic and embodied features
of turns that contain these open personal forms and examine their sequential positioning. We show that the 1st and 2nd person forms that receive a deictically open interpretation typically occur in assessments, accounts of personal experience, and imaginary descriptions. They function as deictic displacements, shifting the origo of the speech situation, and causing a change of footing in the discourse roles, thus modulating the participation framework of the speech situation.
(Non)referentiality in conversation